Distribution and spatial configuration of holm oak woodlands in the Montesinho/Nogueira site, Portugal - Dias, Rui (2011)
Holm oak (Quercus rotundifolia) is wide spread within the West Mediterranean region. In Portugal, it is distributed across the interior of the country but woodlands of this species are currently rare. Historical factors explain most of the regression of holm oak to areas not suitable for agriculture where woodlands of this species persist in spite of very frequent wild fires. With the purpose of identifying physical factors related to the maintenance of holm oak woodlands in fire prone landscapes, we studied the distribution and spatial configuration of holm oak remnant patches in the Montesinho/Nogueira Natura 2000 Site (PTCON0002), Northeast of Portugal. We mapped holm oak woodlands from aerial photography and existing vegetation cartography and quantified their size, shape and isolation. These woodlands were also described in terms of geology, soils, slope, aspect, distance to streams, and position in the slope. To test for particular patterns we compared woodland distributions for the variables above with distributions of available conditions using a Chi square test statistic. In the Montesinho/Nogueira Site, holm oak remnant woodlands are distributed over 3033ha, representing 2.8% of the study area. They are usually small in size and simple in shape, and occur close to each other. They are very frequently located towards the bottom of very steep slopes, facing West Northwest and East Southeast, and relatively close to ephemeral streams. However, woodlands intercept these streams in just 45% of the cases. The patterns described above do not change when woodlands are considered according to their development stage. Our results confirm the observation that Quercus rotundifolia woodlands are still infrequent and located in areas unsuitable for other activities. Within the areas of current distribution, the woodlands are very fragmented. Besides slope and position in the slope, there are no other factors that seem to affect the distribution of holm oak woodlands. Given that these woodlands occur in areas where wild fires are very frequent, we concluded that other factors need to be considered to explain the observed distribution. This subject is part of a larger ongoing research project on the mechanisms of resistance of holm oak woodlands to wild fires.